Implementasi Sosiodrama dalam Layanan Bimbingan Kelompok untuk Mengembangkan Keterampilan Sosial Siswa - Nawawi, Erfan (CV. Lentera Literasi Indonesia, 2025)
One of the key ingredients to individual success is social skills, which play a significant role in the future whether academically, socially or professionally. Social skills are the ability of individuals to build positive relationships in the social realm both in behavior, speech and attitude. The purpose of this study is to examine the application of group guidance services with sociodrama techniques to develop social skills. Sociodrama is a method that allows students to experience the role of social behavior silently during a simulated situation. The research method used in this research is literature review. Identifying and reviewing from several literatures related to the topic. The results of this study revealed that the implementation of sociodrama in group guidance proved to be effective in develop students' social skills, such as interpersonal relationships, self-confidence, empathy, responsibility and conflict management.